The Denial of Mystery: Object Relations Theory and Religion - Smith, Roy Herndon Steinhoff (Horizons, 1989)
A number of religious thinkers have uncritically made use of psychoanalytic object relations theory. I argue that this uncritical appropriation is dangerous to religious thought because object relations theorists tend, implicitly, if not explicitly, to deny the reality of the object of religious faith or Mystery. I analyze the defenses against Mystery in object relations theory in order to uncover what is denied by them. This critical analysis allows object relations theory to be reappropriated by religious thinkers as a valuable source of insights into the ways Mystery manifests itself in human life.